A comparative study on lateral displacements of movable T-deck and Box-deck under solitary waves. (December 2021) - Chen, Xuebin; Xu, Guoji; Lin, Chong; Sun, Hongwei; Zeng, Xiaofang; Chen, Zhengdong
Abstract: From the field observations of bridge deck failures under extreme waves, it is shown many bridge decks were laterally displaced at varying displacements on the pier caps, and some decks with large lateral displacements even fell into the water. The repair cost varies with the lateral deck displacement, especially between different bridge states (Fixed state, Partially-displaced state, Falling-down state) after the disaster. To the author's knowledge, a comparative study of lateral displacements for T-deck and Box-deck under extreme waves has not been conducted. This paper discusses some fundamental questions related with the lateral deck displacement: (1) What are the influences of three essential parameters (relative clearance, wave height, deck weight) on the lateral displacements for two kinds of bridge decks? (2) Which kind of bridge deck is safer under the extreme solitary waves? In other words, is the lateral displacement of T-deck always larger or smaller than the Box-deck? (3) Does a larger horizontal or vertical wave force on two decks always induce a fiercer lateral motion response? (4) What is the most vulnerable condition for the failures of T-deck and Box-deck? Motivated by these questions, a comparative research on the wave-deck interactions for two movable decks under solitary waves is conducted by a numerical model solving the Navier-Stokes equations. A total of 330 numerical experiments based on this model have been designed to dynamically study the lateral responses of two bridge shapes under various conditions. This study provides researchers an insight into the dynamic properties for T-deck and Box-deck under solitary waves, and improves our understanding of the fragility of two decks under extreme waves.